2018
DOI: 10.1016/j.radcr.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hepatic hemangiomatosis in 2 septuagenarians

Abstract: We report 2 cases of isolated hepatic hemangiomatosis: a 76-year-old woman who is, to our knowledge, the oldest person with this diagnosis, and a 74-year-old woman. Magnetic resonance imaging of the abdomen showed T2 hyper intense lesions throughout the liver, peripheral nodular arterial enhancement, and filling of contrast on the portal venous and delayed phases. Computed tomography showed liver lesions with peripheral nodular enhancement in the early phase and a centripetal pattern or “filling in” during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…3 ). These characteristics were consistent with the diagnosis of liver hemangiomatosis [6] and biopsy was not performed due to the absence of chronic liver disease, normal laboratory tests and the evaluation of the imaging of the liver that showed the vascular nature of the lesions.
Fig.
…”
Section: Case Reportmentioning
confidence: 55%
See 1 more Smart Citation
“…3 ). These characteristics were consistent with the diagnosis of liver hemangiomatosis [6] and biopsy was not performed due to the absence of chronic liver disease, normal laboratory tests and the evaluation of the imaging of the liver that showed the vascular nature of the lesions.
Fig.
…”
Section: Case Reportmentioning
confidence: 55%
“…In 2018, Liu et al. Little presented two cases of isolated hepatic hemangiomatosis, and included a review of 15 other cases of isolated hepatic hemangiomatosis reported in English literature from 1970 up to that moment (July 2018) [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic hemangiomatosis is an uncommon disorder characterized by the proliferation of numerous hepatic hemangiomas dispersed throughout the liver parenchyma. Although typically asymptomatic in adults, hemangiomatosis is more commonly observed in newborns, where it can be associated with congestive heart failure [ 56 , 57 ]. Unlike the presentation of multiple discrete hepatic hemangiomas, hemangiomatosis features lesions that are ill-defined, extensive, and confluent, potentially encompassing the majority of the hepatic parenchyma.…”
Section: Atypical Hepatic Hemangiomas In Imagingmentioning
confidence: 99%
“…However, MRI retains its diagnostic utility in these cases, as T1- and T2-weighted sequences reveal distinctive signal patterns. Despite heterogeneous enhancement in the arterial phase, these lesions demonstrate progressive enhancement in dynamic late phases, maintaining typical signal intensities on T1- and T2-weighted MR sequences [ 43 , 46 , 56 , 57 ].…”
Section: Atypical Hepatic Hemangiomas In Imagingmentioning
confidence: 99%
“…Thus, the natural history of hepatic hemangiomatosis is also important in determining a treatment for hepatic hemangioma. However, the natural history of hepatic hemangiomatosis remains largely unknown [ 18 , 19 ]. This study aimed to evaluate the natural history of hepatic hemangiomas >10 cm in size.…”
Section: Introductionmentioning
confidence: 99%